The Influence of Compensation and Non-Physical Work Environment on Employee's Productivity Through Extrinsic Motivation at CV Samudra Kiat Jaya - Jowantoro, Christian Samuel; Subadi, Lucky Cahyana (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study investigates the relationship between compensation, non-physical work environment, extrinsic motivation, and employee productivity at CV Samudra Kiat Jaya, A coconut briquette manufacturer in Sidoarjo, East Java, Indonesia. Analysis of the internal data from August 2023 to February 2024 reveals concerning fluctuations in productivity levels, alongside an employee turnover rate of 13.5%, indicating potential performance issues within the workforces. Employing an explanatory qualitative research design, this study uses partial least Square – Structural Equation Model (PLS-SEM) for data analysis, with an employee sample of 72 collected via Google Forms. Findings demonstrate that both compensation and non-physical work environment positively and significantly influence extrinsic motivation among employees. Furthermore, extrinsic motivation is shown to enhance employee productivity significantly, with both compensations and non-physical work environments exerting a positive impact on productivity indirectly through extrinsic motivation. These results underline the importance of effective compensation strategies and a supportive non-physical work environment in enhancing employee performance and retention, ultimately benefiting the organization’s productivity levels.